Ebanga™: The most recent FDA-approved drug for treating Ebola - Taki, Elahe; Ghanavati, Roya; Navidifar, Tahereh; Dashtbin, Shirin; Heidary, Mohsen; Moghadamnia, Marjan (Frontiers in Pharmacology, 2023)
The Ebola virus (EV) is a virulent pathogen related to a life-threatening disease in human with fatality rates of up to 90%. Since the first discovered outbreak in Africa, EV has led to several outbreaks particularly in the last few decades. Even though the Ebola virus disease (EVD) considers as a serious threat to the human and the outbreaks occur almost every year, the treatment options for EVD are limited. In the way of development of therapeutic strategies against EV, the viral structural proteins such as glycoprotein (GP) were the most attractive targets to neutralize virus. According to the latest research, GP-specific antibodies are the most efficient post-exposure treatments for EVD. Ansuvimab-zykl or mAb114 (EbangaTM) is a recent FDA-approved human immunoglobulin monoclonal antibody targets EV GP. We attempt to provide a brief overview of pharmacological effects and safety profile of Ansuvimab in clinical trials as well as the precise mechanism of this new drug to treatment of EVD in this review article.